SEROPREVALENCE OF LEPTOSPIROSIS AND ITS ASSOCIATION WITH REPRODUCTIVE AND PRODUCTIVE PARAMETERS FROM BUFFALO POPULATION OF RAJANPUR AND MUZAFFARGARH DISTRICTS OF PAKISTAN - M. Ijaz; A. Ghaffar; A. Ali; S. H. Farooqi; Y. R. Khan; A. I. Aqib (Journal of Animal and Plant Sciences, 2020)
Leptospirosis is one of the important infectious diseases adversely affecting the fertility and reproductive parameters of domestic animals. The current study was aimed to investigate the sero-prevalence of leptospirosis and its association with reproductive and productive parameters from buffalo population of Rajanpur and Muzaffargarh districts of Punjab, Pakistan. A total of 386 buffalo serum samples were analyzed for anti-leptospira antibodies through indirect ELISA using “Anti-Leptospira IgG kit”. The information regarding disease determinants were captured in questionnaire. Univariable and multivariable logistic regression models were used to correlate the potential risk factors with the disease dynamics. The results revealed an overall 12.69% prevalence of leptospirosis in both of the study districts, with higher percentage reported in district Rajanpur followed by Muzaffargarh presenting 20.72 and 04.66% prevalence at significant difference (p≤0.05), respectively. The univariable analysis found district, estrus repetition, body condition score and history of retained placenta as significant candidates (p ≤ 0.05) while, multivariable logistic regression presented district, gender of animal and estrus repetition as the key risk factors (Odds Ratio>1). The study concluded that leptospirosis is prevalent in study districts and there is association of assumed risk factors with disease dynamics, which demands early installment of control strategies before the disease become unleashed.
Keywords: Leptospirosis; Sero-prevalence; Risk factors; Buffalos